Spatial and Temporal Analysis of Earthquake Events in Kahramanmaraş on 6 February 2023 - Özer Akyürek (Doğal Afetler ve Çevre Dergisi)
Earthquakes are one of the most destructive natural disasters that occur as a result of the energy resulting from the movements of the earth's crust spreading and shaking the earth's surface. Since it is not possible to predict when and where earthquakes will occur, it has become possible to make various inferences and take necessary precautions by analyzing previous earthquakes. Spatial and temporal analysis of natural disasters such as earthquakes with geographic information systems provides useful information to local and global decision-makers in measures to be taken and mitigation studies. The objective of this study is to demonstrate that the general orientation of stress accumulation on fault lines can be monitored by weighted average centre points with the use of Geographic Information Systems (GIS). Spatio-temporal analyses of two earthquakes with a magnitude of 7.7 Mw and 7.6 Mw in Kahramanmaraş and aftershocks were performed. Ten-week spatial distributions of the aftershocks were examined with the weighted average center method and it was determined that the earthquake intensity and average centers shifted towards the north. When the spatial distribution of the earthquake centers is examined with the help of standard deviation ellipses weekly, it has been determined that they show orientation along the Eastern Anatolian Fault System.